Social sustainability for business - Carbo, Jerry A. 1972-; Dao, Viet; Haase, Steven J.; Hargrove, M. Blake; Langella, Ian M. (Routledge, 2018)
Introduction to socially sustainable business systems (SSBS) -- Business practices of DAC -- The advent of socially sustainable business systems -- Socially sustainable business systems -- Socially sustainable business systems, employee relations, HR management and employment policy -- Sustainable operations management -- Sustainable supply chains -- IT and sustainability -- Leadership for sustainability -- Strategy and ssbs -- Psychology and socially sustainable business systems -- Why are we tied to destructive advanced capitalism? -- How do we break the ties and move forward?